2008
DOI: 10.1002/gps.1984
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease in real life – the dementia carer's survey

Abstract: Further development of services and information provision are required to help carers in their everyday caring, including coping with problematic symptoms influencing areas such as activities of daily living and behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
0
14

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 16 publications
11
122
0
14
Order By: Relevance
“…The response rate was more than 20%. This value corresponds exactly with the empirically established response in anonymous written surveys of family caregivers who received no reward for answering (Georges et al 2008;Gräßel 2002). However, a recruitment bias cannot be ruled out.…”
Section: Structural Quality (S): Non-personal Factors (S I); Person-rsupporting
confidence: 73%
“…The response rate was more than 20%. This value corresponds exactly with the empirically established response in anonymous written surveys of family caregivers who received no reward for answering (Georges et al 2008;Gräßel 2002). However, a recruitment bias cannot be ruled out.…”
Section: Structural Quality (S): Non-personal Factors (S I); Person-rsupporting
confidence: 73%
“…Moreover, we have to underline that the comprehensive geriatric assessment we performed also considered objective determinants of the Only about 11% of our sample of depressed older adults were attending a DC. This seems to be a low rate of attendance, yet if we compare it with the rate of attendance of DCs (both regular and specific DCs) in all communitydwelling subjects with dementia (28%) (Georges et al 2008), we believe we have found results of a reasonable magnitude taking into account that: (i) dementia and depression have a similar prevalence in the communitydwelling older population (Ferri et al 2005;Unutzer 2007),…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, even in the hypothesis that a higher weekly attendance of DCs is actually able to improve the QOL in (Georges et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In one study, 89% to 96% of caregivers reported that elderly care recipients had behavioral problems and problems with ADLs (Georges et al, 2008). The caregiver burden for a person with dementia has been associated with decreased psychological and physical well-being of the caregiver (Bell, Araki, & Neumann, 2001;George & Gwyther, 1986;Hooker et al, 2002;Shaw et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, depression has been reported to occur among 1 in 4 family caregivers (Machida & Hosaka, 2006). In particular, caring for elderly people with dementia who have behavioral problems and/or problems with activities of daily living (ADLs) is associated with a high risk of caregiver burden and depression (Georges et al, 2008;S.H. Zarit, Todd, & J.M.…”
Section: Introductionmentioning
confidence: 99%